O-GlcNAc regulates the mitochondrial integrated stress response by regulating ATF4 - Alghusen, Ibtihal M.; Carman, Marisa S.; Wilkins, Heather; Ephrame, Sophiya John; Qiang, Amy; Dias, Wagner B.; Fedosyuk, Halyna; Denson, Aspin R.; Swerdlow, Russell H.; Slawson, Chad (Frontiers in Aging Neuroscience, 2023)
Accumulation of mitochondrial dysfunctional is a hallmark of age-related neurodegeneration including Alzheimer's disease (AD). Impairment of mitochondrial quality control mechanisms leading to the accumulation of damaged mitochondria and increasing neuronal stress. Therefore, investigating the basic mechanisms of how mitochondrial homeostasis is regulated is essential. Herein, our data establishes an essential role of O-GlcNAcylation, a single sugar posttranslational modification, in controlling mitochondrial stress-induced transcription factor Activating Transcription Factor 4 (ATF4). Mitochondrial dysfunction triggers the integrated stress response (ISR mt ), in which the phosphorylation of eukaryotic translation initiation factor 2α results in the translation of ATF4. We show that sustained O-GlcNAcase inhibition by Thiamet-G (TMG) in SH-SY5Y neuroblastoma and HeLa cell-lines elevates ATF4 protein levels upon mitochondrial stress. An indirect downstream target of ATF4 mitochondrial chaperone glucose-regulated protein 75 (GRP75) is significantly elevated. Interestingly, knock-down of O-GlcNAc transferase (OGT), the enzyme that adds O-GlcNAc, in SH-SY5Y increases ATF4 protein and mRNA expression. Additionally, ATF4 target gene Activating Transcription Factor 5 (ATF5) is significantly elevated at both the protein and mRNA level. Brains isolated from TMG treated mice show elevated levels of ATF4 and GRP75. Importantly, ATF4 occupancy increases at the ATF5 promoter site in brains isolated from TMG treated mice suggesting that O-GlcNAc is regulating ATF4 targeted gene expression. Interestingly, ATF4 and GRP75 are not induced in TMG treated familial Alzheimer's Disease mice model. The same results are seen in a human In-vitro model of AD. Together, these results indicate that in healthy conditions, O-GlcNAc regulates the ISR mt through regulating ATF4.